Islamic Heritage Site: Up-Scaling Halal Tourism with Augmented Reality Technology at Sunan Giri Pilgrimage in Gresik - Himawan, Abdurrahman Faris Indriya; Mita Kharisma; Awang Setiawan Wicaksono; Umaimah; Abdul Kholid Achmad (Society : Jurnal Pengabdian Masyarakat, 2026)
The pilgrimage of Wali Songo, especially the Tomb of Sunan Giri in Gresik, is a religious tourist destination with millions of visits per year that holds extraordinary economic and spiritual potential. However, the method of conveying historical information is still conventional and limited. The Community Service Program (Abdimas) aims to develop an Augmented Reality (AR)-based mobile application platform that integrates three main focuses: (1) visualization of the historical site of the Sunan Giri Tomb and the Giri Kedaton Kingdom in three dimensions; (2) a digital directory of MSMEs and geospatial-based local products; and (3) transportation and accommodation guides for pilgrims. The implementation method uses a Participatory Action Research (PAR) approach for six months, involving collaboration between Telkom University, Muhammadiyah Gresik University (UMG), Giri Village Government, and Tourism Awareness Group (Pokdarwis). The results of the evaluation showed an increase in visitor engagement by 47%, understanding of historical content increased by 62%, and the turnover of partner MSMEs increased by an average of 35%. AR applications have succeeded in encouraging the organic viral marketing ecosystem through social media sharing content. This program emphasizes that AR technology is able to be a bridge between the preservation of Islamic historical heritage and the acceleration of sustainable digital halal tourism in the Society 5.0 era.